Supporting shop floor workers with a multimedia task-oriented information system - Tjahjono, Benny (Elsevier Science B.V., Amsterdam., 2009)
This paper reports the work carried out as part of an industrial research project sponsored by a major telecommunication industry based in the UK. The main aim of the research was to investigate the extent to which a multimedia- based information system, developed for shop floor workers, has contributed to the increased efficiency and productivity Of manufacturing operations. To achieve this, the work has focused on the design and execution of the evaluation of the system. Due to the fact that the direct impact of the implementation of the information system developed was difficult to demonstrate, it was decided to adopt the system usage as a surrogate of the system's Success and the User acceptance of the system was evaluated using both the Technology Acceptance Model and the Task-Technology Fit model. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Standardised work Information Support System Usability Technology Acceptance Model Task-Technology Fit user evaluations technology usability